Respuesta :

Answer:

B. x≥-3

Step-by-step explanation:

To solve this problem, first you have to isolate it one one side of the equation.  

First, multiply -1 from both sides.

(-9x)(-1)≥27(-1)

Solve.

27*-1=-27

9x≥-27

Next, divide by 9 from both sides.

9x/9≥-27/9

Then, solve.

-27/9=-3

Therefore, the correct answer is x≥-3.

For this case we must find the solution of the following inequality:

[tex]-9x \leq27[/tex]

If we divide by -9 on both sides of the inequality we have:

[tex]-x \leq \frac {27} {9}\\-x \leq3[/tex]

If we divide by -1 on both sides of the inequality, the sense of it changes:

[tex]x \geq-3[/tex]

ANswer:

Option B